Experimental investigation on flue gas purification and gas‐liquid multiphase flow in a spraying column with perforated plate. (7th January 2020) - Chen, Zhen; Jiang, Zhiqiang; You, Changfu; Wang, Haiming
Abstract: The synergetic removal of sulphur dioxide and particulate matters (PM) in flue gas was investigated in a spraying column equipped with flow pattern controlling (FPC) internals. The performance of the novel column was compared with that of the traditional open column by monitoring the removal efficiency and system pressure drop. To understand the gas‐liquid multiphase flow field and mass transfer process inside the column with different structures, image processing based on the Otsu method and particle image velocimetry (PIV) technology were used. It was found that the FPC column with a section size of 200 mm × 200 mm, hole diameter of 4 mm, and aperture ratio of 0.65 demonstrated the best performance. As clearly observed from the flow filed, bubble flow was formed in FPC column, while the dispersive and falling‐film flow was developed in the open column. The liquid holdup in FPC unit was much more than in the open spraying column, which enhanced the mass transfer process. According to the PIV results, the reverse flow of the liquid, caused by the gas jet ascribed to the perforated plate and the confined space in the FPC unit, was the primary reason for bubble generation and the gas‐liquid flow pattern in the column.